The mutation of the contentious administrative process and its effectiveness in Peruvian law - Guerra Cerrón, J. María Elena (2018)
The present paper seeks to give, in the first place, a brief historical review of the origin and development of contentious administrative process, his location on Peruvian law frame and his function. Also, it gives a critical analysis to show if this process is serving the purpose given, that is protecting the rights and interests of the governed.